"Falling into the urban trap?" : practices of international Non Government Organisations in East Timor - Roy, Dallas (Massey University, 2002)
The intention of this research project is to draw comparison and contrast of the six biases associated with urban trap of development, against the relevant practice of 20 International non-government organisations (INGOs) operating in East Timor. This will occur through a number of chapters. Firstly the setting for the research project and background to East Timar will be laid out. The second chapter will give explanation of the theory. There will then be chapters describing methods utilised to obtain research and a summation of the research. Finally the research project will culminate with analyse of the theory against the practice.--From Introduction